The purposes of evaluation in mathematics fairs - Scheller, Morgana; Zabel, Marília [UNESP] (FapUNIFESP (SciELO), 2020)
The Mathematics Fairs Movement is a space that encourages, disseminates, and socializes classroom experiences, research and mathematical activities developed mainly in Basic Education. Santa Catarina has already had 35 editions of the fair and, recently, has been standing out on the national scene. In this Movement, the evaluation process has always been controversial due to the indication result of the works and the qualitative description made by the evaluators. Thus, this article sought to understand the meanings that emerge from the evaluation records of the works exhibited at the Fair, based on the evaluation purposes defended in the Movement. It is a qualitative and interpretative research, which investigation process took place through documentary study. The data are made up of the assessment forms that are part of the final report of two Regional Mathematics Fairs held in 2017. Thus, 225 assessment sheets from 71 works were analyzed, through the procedures of the Textual Discursive Analysis (ATD). From the analysis, four categories emerged describing the meanings of the evaluation: evaluation as a means to validate/verify, to measure, to disqualify, and to suggest/propose. It was identified that the evaluations focus on the purposes of examining and rating and that the propositional considerations, characteristic of a formative evaluation, are causally related to the evaluator's conception. We conclude, therefore, that it is necessary to constantly invest in the training of guiding teachers and evaluators who participate in the Movement.
Os propósitos da avaliação nas feiras de matemática
Keywords: Evaluation Conception; Evaluation Sheets; Mathematics Trade Shows